Une enquête socio-démographique auprès des Indiens de la Baie James: 1968 - Piché, Victor; Romaniuk, A. (Anthropologica, 2022)
In this paper, a socio-demographic study of the Indian population of the James Bay area is presented. In the summer of 1968, the authors conducted a survey in six Northern communities: Attawapiskat, Fort Albany, Moosonee, Fort George, Fort Rupert, and Moose Factory. The methodology is explained and the characteristics of the population interviewed are given. Finally, relevant hypotheses based on preliminary findings are discussed.